1994
DOI: 10.1038/eye.1994.112
|View full text |Cite
|
Sign up to set email alerts
|

Back pain in ophthalmologists

Abstract: A questionnaire regarding the working practices and incidence of back pain was sent to all 498 consultant ophthalmologists in the United Kingdom. Three hundred and twenty-five (65.3%) questionnaires were analysed by time spent in speciality, and time spent operating each week. One hundred and seventy-four ophthalmologists (54%) had significant attacks of back pain, with the longest-serving consultants having an increased incidence. The number and duration of acute attacks increased with years in speciality but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 5 publications
2
37
1
1
Order By: Relevance
“…This was consistent with the findings of Chatterjee et al 27 15 Chatterjee et al 27 reported that ophthalmologists with the longest-serving consultants having an increased incidence of LBP and the number and duration of acute attacks increased with years in specialty. In addition, Bejia et al 34 found seniority as a risk factor for LBP.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was consistent with the findings of Chatterjee et al 27 15 Chatterjee et al 27 reported that ophthalmologists with the longest-serving consultants having an increased incidence of LBP and the number and duration of acute attacks increased with years in specialty. In addition, Bejia et al 34 found seniority as a risk factor for LBP.…”
Section: Discussionsupporting
confidence: 89%
“…on LBP have been investigated in different studies. 12,[27][28][29][30] There is very little evidence of gender differences in back pain. According to the review by the CSAG, 31 women report a slightly higher percentage of back pain than men, but at a rate similar to The results of the present study showed no significant difference between male and female surgeons in reporting LBP.…”
Section: Discussionmentioning
confidence: 95%
“…[6][7][8] As a group, the surgeons subjectively noted less neck strain and fatigue using VITOM compared with traditional magnifying loupes alone; however, this finding is limited by lack of objective measures to better quantitate these potential differences. Based on previous studies using VITOM, we speculate that the decreased neck strain and fatigue is the result of improved ergonomics throughout the operations that enabled the surgeon to stand straight upright for hours in a comfortable position, thereby decreasing the need to lean or bend the neck to maintain magnifying loupe focus.…”
Section: Discussionmentioning
confidence: 92%
“…[1][2][3][4][5] Although these magnifying instruments are essential to the optimal care of our patients, they often come at a detriment to the operating surgeon in the form of neck or back pain and fatigue. Furthermore, neck pain, back pain, and fatigue have been studied in multiple surgical disciplines, [6][7][8] but these factors, however, have not yet studied among pediatric surgeons. Drawbacks of traditional magnifying loupes include poor neck posture and frequent head movement to refocus the view, in addition to the inability to share the magnified visual field with surgical residents and assistants.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal pain is common among ophthalmologists and other eye care physicians (Chams et al 2004;Chatterjee et al 1994;Dhimitri et al 2005;Kitzmann et al 2012;Sivak-Callcott et al 2011). In particular, pain and discomfort in the neck and shoulder region is reported more frequently by eye care physicians than peers in other medical specialties (Kitzmann et al 2012).…”
Section: Introductionmentioning
confidence: 98%